EKOLOGI DAN LINGKUNGAN HIDUP DALAM PERSPEKTIF ALQURAN - Zainal Abidin (MIYAH : Jurnal Studi Islam, 2017)
The occurrence of disasters is not only a symptom of nature but is caused by human activity which starts from the absence of a clear understanding of ecology and the environment. As a Muslim who has a life guide book, we must see how the Koran looks at and explains about ecology and the environment. Briefly and simply according to A. Qadir Gassing to see the Islamic concept of nature and environment can be traced to the three key words of the Alquran, namely earth or environment (ard), destruction (al-ifsad) and preservation (al-islah). While Mujiyono Abdullah argues that there are 16 key concepts of ecology and the environment in the perspective of the Alquran. From the many key words that explain the ecology and environment in the Alquran at least provide confirmation to us that the Koran already has concern for the environment before the ecological theory itself is born and formulated by ecologists and environment-alists.Keywords : Alquran, Ecology,Environment